BIOMETRICAL ANALYSIS OF SCAPULA BONE OF FISHING CAT, LEOPARD CAT AND SMALL INDIAN CIVET (Applied Biological Research, 2023)
The fishing cat (Prionailurus viverrinus) is a medium-sized wild cat with a sporadic distribution in  mangroves, wetlands, rivers, and swamps in parts of South and Southeast Asia (Nowell and Jackson,  1996). The fishing cat is in the red list of IUCN as vulnerable (IUCN, 2016). The fishing cat is the  state animal of West Bengal (India). The leopard cat (Prionailurus bengalensis) is a small wild  cat native to the South and East Asia (Ross et al., 2015). Since 2002, it has been assessed as least  concern on the IUCN red list as it is widely distributed but threatened by habitat loss and hunting in  parts of its range (Ross et al., 2015). The small Indian civet (Viverricula indica) is a civet found  in South and Southeast Asia. It is in the least concern list of IUCN because of its wide geographical  distribution (Choudhury et al., 2015). Scapula is an important bone responsible for the movement of  forelimb. The research related to the biometrical analysis of scapula of fishing cat, leopard cat and  small Indian civet are lacking, so the present investigation was conducted.
Keywords: BIOMETRICAL; ANALYSIS; LEOPARD; FISHING